Metal nanopowders : production, characterization, and energetic applications - Gromov, Alexander; Teipel, Ulrich (Weinheim, Germany : Wiley-VCH Verlag, 2014)
Written with both postgraduate students and researchers in academia and industry in mind, this reference covers the chemistry behind metal nanopowders, including production, characterization, oxidation and combustion. The contributions from renowned international scientists working in the field detail applications in technologies, scale-up processes and safety aspects surrounding their handling and storage.
4.3.3 Starting Material Metering Device (Dispenser)4.3.4 Disperse Material Trapping Devices (Cyclone Collectors and Filters); 4.3.5 NP Encapsulation Unit; 4.4 Characteristics of Al Nanopowders; 4.5 Nanopowder Chemical Passivation; 4.6 Microencapsulation of Al Nanoparticles; 4.7 The Process of Producing Nanopowders of Aluminum by Plasma-Based Technology; 4.7.1 Production of Aluminum Nanopowder; 4.7.2 Some Properties of Produced Nanopowders of Aluminum, Boron, Aluminum Boride, and Silicon; References; Chapter 5 Characterization of Metallic Nanoparticle Agglomerates; 5.1 Introduction.
Includes bibliographical references at the end of each chapters and index.
Online resource; title from PDF title page (Wiley, viewed June 4, 2014).
Keywords: Metal powders; Nanostructured materials; Liquid metals; Metal powders; Nanopowders; Nanostructured materials; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; Metal powders; Nanostructured materials; Electronic books